Table of Content - - (Journal of engineering sciences and information technology, 2024)
Table of Content: 1. A Glimpse into the Future of Quantum Computing and AI Eng. Fayyad Mohammed Hani Bayan 2. Designing a Hybrid System based on between Deep learning Network with Face Detection algorithm for Emotion Recognition through Facial Features Analysis Mohamad Bashir Amir Nahas, Asst-Prof. Lara Fathi Kadid, lecturer Mohamad Ahmad Mounir Batikh 3. Deductive analysis for Municipalities of Baghdad city, within the healthy city program Dr. Heyam Hameed Abdul-majeed Ali 4. Preparing a cost control plan for a contracting company VR:00 (05-2019) Eng. Mohamad Muhanad Ahmad Senjab 5. Evaluation of design quality and its impact on execution in private housing projects in Kuwait Eng. Sadeq Yahya Bumejdad, Eng. Mohamed Ezzat Elnakhely 6. Investigating the Water Demand and Supply Situation in Baljurashi Governorate, Saudi Arabia Dr. Gamal Khalid Awadelkarim Mohamed, Dr. Osman Mohamed Najjar Ali, Dr. Ali Khalaf Ahmed Al-Baggar, Prof. Hasan Saad Mohammed Hilmi 7. Review on building energy effeciency through optimized building envelopes Ms. Maryam Omar Bazaraah, Prof. Laila Khodeir, Dr. Mahmoud Gadelhak 8. Requirements to Improve the Technical Support at Umm Al-Qura University (2019) (Concept Proposal) Eng. Reem Metlea Mohamed Alqahtani, Eng. Reham Zahir Omar Almarghlani